Diabetes: a metabolic and reproductive disorder in women. Issue 2 (February 2020) - Thong, Eleanor P; Codner, Ethel; Laven, Joop S E; Teede, Helena
Summary: Reproductive dysfunction is a common but little studied complication of diabetes. The spectrum of reproductive health problems in diabetes is broad, and encompasses delayed puberty and menarche, menstrual cycle abnormalities, subfertility, adverse pregnancy outcomes, and potentially early menopause. Depending on the age at diagnosis of diabetes, reproductive problems can manifest early on in puberty, emerge later when fertility is desired, or occur during the climacteric period. Historically, women with type 1 diabetes have frequently had amenorrhoea and infertility, due to central hypogonadism. With the intensification of insulin therapy and improved metabolic control, these problems have declined, but do persist. Additional reproductive implications of contemporary diabetes management are now emerging, including polycystic ovary syndrome and hyperandrogenism, which are underpinned by insulin action on the ovary. The sharp rise in type 2 diabetes incidence in youth suggests that more women of reproductive age will encounter diabetes-related reproductive problems in their lifetimes. With an ever increasing number of young women living with diabetes, clinicians need to be aware of and equipped for the challenges of navigating reproductive health concerns across the lifespan.